What can management accounting practitioners and academics do to improve risk measurement and forewarn impending financial crises? / Sriya Kumarasinghe and Roger Willett - Kumarasinghe, Sriya; Roger, Willett (Accounting Research Institute (ARI), 2010)
We discuss some perceived shortcomings of management accounting in the light of the financial crisis of 2008. We describe current trends in management accounting thinking and Japanese perspectives on the discipline. Our main focus is on the lack of reliable measurement of financial risk and its consequences. The importance of collaborative multi-disciplinary research through partnerships between academics and practitioners is emphasised.